Early Childhood Exposure to Intimate Partner Violence and Developmental Vulnerability at Kindergarten: Linking Canadian Population-Level Administrative Data. - Lee, Janelle Boram; Nickel, Nathan; Afifi, Tracie; Turnbull, Lorna; Urquia, Marcelo; Brownell, Marni (International Journal of Population Data Science, 2022)
Objective The objective was to examine the relationship between maternal intimate partner violence (IPV) victimization and children’s developmental health using linked population-wide administrative datasets. We examined developmental vulnerability (DV) at kindergarten of children exposed to maternal IPV victimization aged 0 to 5 using provincial prosecution records compared to unexposed counterparts. Approach This retrospective cohort study linked administrative datasets (legal, health, education, social services) from the Population Research Data Repository at the Manitoba Centre for Health Policy. Exposed mother-child pairs with 1+ prosecution records of maternal IPV victimization during early childhood (child aged 0 to 5) between 2003-2018 in Manitoba (n = 5,728) were matched to unexposed pairs (1:3) based on sex/birthdate of child and neighbourhood income. DV at kindergarten was measured across 5 domains (physical, social, emotional, language/cognitive [LC], communication/general knowledge) using the Early Developmental Instrument (EDI). Children without eligible EDI scores were excluded. Multiple logistic regression models were conducted. Results The cohort included 5321 children (exposed n=1365, unexposed n=3956). 32.98% of the cohort was developmentally vulnerable in one or more domains (1/+) and 19.60% was developmentally vulnerable in two or more domains (2/+). Unadjusted relationships between maternal IPV victimization from age 0 to 5 and developmental vulnerability at kindergarten were statistically significant across all 5 domains (e.g., LC OR=2.76 [2.36, 3.23]) and in 1/+ (OR=2.72 [2.39, 3.09]) as well as 2/+ (OR=2.89 [2.51, 3.34]) domains. After adjusting for covariates, children who were exposed to maternal IPV victimization from ages 0 to 5 had increased odds of being developmentally vulnerable in social competence (aOR=1.33 [1.07, 1.66]) and emotional maturity (aOR=1.29 [1.03, 1.62]), also in 2/+ domains (aOR=1.42 [1.15, 1.73]) at kindergarten, compared to unexposed counterparts. Conclusion The study provided Canadian population-wide evidence of the association between maternal IPV victimization and early childhood development, specifically later socio-emotional vulnerability. Interventions and support systems for this population of families should be developed and implemented, with an emphasis on mitigating long-term socio-emotional developmental risks in children exposed to IPV.